Students' experience of using youtube in learning business accounting / Zulnaidi Yaacob and Nor Hasliza Md Saad. - Yaacob, Zulnaidi; Md Saad, Nor Hasliza (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
The literature is replete with positive reviews of using Internet 2.0 in teaching and learning. The use of Internet 2.0, such as YouTube, has attracted millions of users including students and teachers. The growing number of YouTube users and what YouTube can offer in improving learning experience have attracted significant interest of many researchers on the possibility of integrating YouTube in learning activities. However, factors that influence students' use of YouTube in learning is less explored in the literatures. Hence, this study aims to identify the factors that influence students' experience in using YouTube as their learning platform. Data were collected from 342 students and the findings reported that, perceived usefulness, perceived ease of use, and social influence are three important factors in encouraging respondents to use YouTube as a learning platform. The implications of this study are also discussed, together with the limitations and suggestions for future research.